Coffea arabica L., a new host plant for Acetobacter diazotrophicus, and isolation of other nitrogen-fixing acetobacteria. - Jimenez-Salgado, T (1997)
Acetobacter diazotrophicus was isolated from coffee plant tissues and from rhizosphere soils. Isolation frequencies ranged from 15 to 40% and were dependent on soil pH. Attempts to isolate this bacterial species from coffee fruit, from inside vesicular-arbuscular mycorrhizal fungi spores, or from mealybugs (Planococcus citri) associated with coffee plants were not successful. Other acid-producing diazotrophic bacteria were recovered with frequencies of 20% from the coffee rhizosphere. These N2-fixing isolates had some features in common with the genus Acetobacter but should not be assigned to the species Acetobacter diazotrophicus because they differed from A. diazotrophicus in morphological and biochemical traits and were largely divergent in electrophoretic mobility patterns of metabolic enzymes at coefficients of genetic distance as high as 0.950. In addition, these N2-fixing acetobacteria differed in the small-subunit rRNA restriction fragment length polymorphism patterns obtained with EcoRI, and they exhibited very low DNA-DNA homology levels, ranging from 11 to 15% with the A. diazotrophicus reference strain PAI 5T. Thus, some of the diazotrophic acetobacteria recovered from the rhizosphere of coffee plants may be regarded as N2-fixing species of the genus Acetobacter other than A. diazotrophicus. Endophytic diazotrophic bacteria may be more prevalent than previously thought, and perhaps there are many more potentially beneficial N2-fixing bacteria which can be isolated from other agronomically important crops.